2004
DOI: 10.1021/jf030776u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucosinolates and Their Enzymatic Hydrolysis Products via Myrosinase on the Root-knot Nematode Meloidogyne incognita (Kofoid et White) Chitw.

Abstract: The root-knot nematode Meloidogyne incognita (Kofoid et White) Chitw. is responsible for large yield losses in several horticultural crops. Fumigation with chemicals has been efficient in fighting this soil pest, but it clearly shows a negative environmental impact. Thus, it is necessary to find an environmentally friendly alternative to control this nematode and meet the requirements imposed by world regulation to ban some chemical fumigants in the world after 2005. The glucosinolate-myrosinase system, typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 23 publications
3
76
0
4
Order By: Relevance
“…Research has also been conducted on the efficacy of biofumigation on Meloidogyne spp. suppression (Lazzeri et al, 2004a;2004b;Riga & Collins, 2004). In future research it would be advantageous if a specific lethal concentration could be determined for the constant effective suppression of the Meloidogyne species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also been conducted on the efficacy of biofumigation on Meloidogyne spp. suppression (Lazzeri et al, 2004a;2004b;Riga & Collins, 2004). In future research it would be advantageous if a specific lethal concentration could be determined for the constant effective suppression of the Meloidogyne species.…”
Section: Discussionmentioning
confidence: 99%
“…(Widmer et al, 2002;Pieters, 2006). A well-documented role of green manure is the biocidal effect that it has on soilborne diseases, nematodes and weeds, which is the result of certain biologically active compounds that are released during the maceration and incorporation processes of green manures, with specific reference to Brassicaceae plants and biofumigation (Brown & Morra, 1997;Sarwar et al, 1998;Lazzeri et al, 2004a;Matthiessen & Kirkegaard, 2006). The technique, defined as biofumigation, relies on the fumigant action of volatile compounds released during biodegradation for the suppression of plant pathogens (Piedra Buena et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Upon tissue damage, glucosinolates are degraded by the enzyme myrosinase, thereby forming toxic breakdown products such as (iso)thiocyanates (Wang et al 2009). Belowground, glucosinolates and their breakdown products are known to reduce the abundance of phytophagous organisms such as rootfeeding nematodes (Lazzeri et al 2004;Potter et al 1998;Potter et al 2000), fungi (Bressan et al 2009;Rumberger and Marschner 2003;Snapp et al 2007), and bacteria (Aires et al 2009;Bressan et al 2009;Rumberger and Marschner 2003). Aromatic glucosinolates, particularly gluconasturtiin and its breakdown product 2-phenylethyl isothiocyanate, are generally considered as the most toxic glucosinolates in plant roots (Potter et al 1998;Potter et al 2000;Rumberger and Marschner 2003;van Dam et al 2009;Vierheilig et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Strong nematicidal activity of isothiocyanates derived from sinigrin (2-propenyl isothiocyanate) was reported in vitro on juveniles of H. schachtii after 24 hours at 0.5% concentration (Lazzeri et al, 1993). Lazzeri et al, (2004) demonstrated stronger activity of the isothiocyanate on M. incognita in vitro. Aside from plant-parasitic nematodes, sinigrin isothiocyanate showed also high biocidal activity on other soil-borne pathogens (Mayton et al, 1996) Glucosativin (4-mercaptobutyl), glucoerucin (4-methylthiobutyl) and glucoraphanin (4-methylsulfinylbutyl) are the most prominent glucosinolates within the leaf tissue of Eruca species (Pasini et al, 2011; Villatoro-Pulido et al, 2013).…”
Section: Discussion:-mentioning
confidence: 99%